FEASIBILITY OF STOCK SEED WATERMELON FARMING ON SANDY AND SANDY LOAM SOIL FARMER PARTNERS OF PT. BENIH CITRA ASIA - Ilmi, Noviatul; Yuswita, Effy; Dewi, Heptari Elita (Socio-Economics/Agribusiness Department, 2024)
The research aims to analyze partnership patterns, income and feasibility of farming, as well as compare the income of partner farmers on sandy and sandy loam soils. This research was conducted in Paseban Village and Sanenrejo Village. The method used is descriptive quantitative by taking a sample of 30 partner farmers by census. Primary data was collected through interviews with questionnaires, while secondary data came from agencies related to the research. Data analysis uses income and feasibility analysis using the R/C ratio, BEP unit and BEP price. To find out the comparison of average income, the SPSS analysis tool was used with the Mann Whitney test. The research results show that the partnership pattern that exists between partner farmers and PT. Benih Citra Asia is a sub-contract partnership pattern. The income from farming watermelon seeds on sandy soil is IDR 13,510,870/ha, and on sandy loam soil IDR 16,495,867/ha. The R/C ratio value of partner farmers for sandy soil and sandy loam is >1, namely sandy soil is 1.235 and sandy loam is 1.468. It is known that the unit BEP value for sandy soil is 21.386 kg/ha and sandy loam soil is 16.519 kg/ha. The BEP price value is IDR 2,901,468/kg on sandy soil and IDR 1,858,364/kg on sandy loam soil. Farming carried out by partner farmers makes a profit and is worth pursuing. There is no difference in income between partner farmers on sandy and sandy loam soil.